Answer:
[tex]x = 3[/tex] and [tex]y = 4[/tex]
Step-by-step explanation:
Given
[Correct Question]
[tex]x^2 - 2y = 1[/tex]
[tex]x^2 + 5y = 29[/tex]
Required
Solve using elimination
First, we eliminate x.
Subtract equation (1) from (2)
[tex]x^2 - x^2 + 5y - (-2y) = 29 - 1\\[/tex]
[tex]5y - (-2y) = 28[/tex]
[tex]5y +2y = 28[/tex]
[tex]7y = 28[/tex]
Divide through ny 7
[tex]y = 4[/tex]
Take [tex]x^2 - 2y = 1[/tex]
Make x^2 the subject
[tex]x^2 = 1 + 2y[/tex]
Substitute 4 for y
[tex]x^2 = 1 + 2*4[/tex]
[tex]x^2 = 1 + 8[/tex]
[tex]x^2 = 9[/tex]
Take square roots
[tex]x = \sqrt 9[/tex]
[tex]x = 3[/tex]